Void by Law, Alive in Practice: Measuring Prohibited Standard Clauses in Twenty Indonesian Digital-Platform Contracts under Article 18 - Dian Rahayu; Ahmad Badruddin; Evelyn Wang (Enigma Institute, 2025)
Article 18 of Indonesia's Consumer Protection Law (Law No. 8 of 1999) prohibits eight categories of standard-form clause, headed by the exoneration clause, and declares them void by law (batal demi hukum). Indonesian scholarship asserts that such clauses pervade digital consumer contracts, yet systematic cross-sector measurement is scarce. This article develops a replicable detection protocol and applies it to the terms of twenty Indonesian digital-platform applications across fifteen sub-sectors. Using a quantitative content-analysis design within empirical legal studies, Article 18 was operationalised into six statutorily anchored clause categories; full public terms were retrieved and read, each category coded present or absent, and every positive code corroborated by verbatim quotation. Every application (20/20; 100 per cent, exact 95 per cent CI 83.2–100.0) contained at least one clause prima facie void under Article 18. Liability-exemption and unilateral-amendment clauses appeared in all twenty; indemnity or waiver clauses in 95 per cent; exclusive-forum terms in 90 per cent; discretionary-termination clauses in 85 per cent; refusal-of-refund clauses in 70 per cent. Applications carried on average 5.40 of six prohibited categories (SD 0.99). Grammatical, systematic, teleological and historical interpretation yield one diagnosis: prohibition, automatic nullity, criminal sanction and a standing supervisory mandate under Article 52(c) are all formally present, yet none operates on drafting conduct. The deficit is institutional, not normative. Comparison with the European Union, the United Kingdom, Australia and Taiwan, and with the Government's own Academic Paper for a replacement Bill, supports six reforms centred on ex ante supervisory clause auditing.